2005
DOI: 10.1080/02652040400026392
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surfactant HLB and different formulation variables on the properties of poly-D,L-lactide microspheres of naltrexone prepared by double emulsion technique

Abstract: The aim of this work was to investigate the role of HLB of emulsifier as well as volume of the internal aqueous phase (W(1)) and presence of salt in the external aqueous phase (W(2)) on the morphology, size and encapsulation efficiency of poly(D,L-lactide) microspheres containing naltrexone HCl. PLA microparticles containing naltrexone HCl, an effective opiate antagonist, were prepared by a water-in-oil-in-water emulsification-solvent evaporation procedure. One of the five different emulsifiers: span 80, span … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 31 publications
7
46
0
3
Order By: Relevance
“…Various other additives to the system have been shown to improve the encapsulation and subsequent release of hydrophilic compounds. Addition of salt to the outer aqueous phase decreases the proportion of partitioned protein by depressing its aqueous solubility (Dinarvand et al, 2005). Alternatively, spray drying has been effectively used to encapsulate insulin in PLGA microparticles with reported minimal denaturation of the protein upon release (Quiglia et al, 2003).…”
Section: Release Of -Chymotrypsin From Optimised Particlesmentioning
confidence: 99%
“…Various other additives to the system have been shown to improve the encapsulation and subsequent release of hydrophilic compounds. Addition of salt to the outer aqueous phase decreases the proportion of partitioned protein by depressing its aqueous solubility (Dinarvand et al, 2005). Alternatively, spray drying has been effectively used to encapsulate insulin in PLGA microparticles with reported minimal denaturation of the protein upon release (Quiglia et al, 2003).…”
Section: Release Of -Chymotrypsin From Optimised Particlesmentioning
confidence: 99%
“…The technique requires surfactant as the main component in the fabrication. A number of studies employing the technique have shown that surfactants had effects on the particle physical aging [2], internal structure [3] and morphological characteristics, [4].…”
Section: Introductionmentioning
confidence: 99%
“…Reported attempts to preserve the pDNA integrity included freezing of the primary emulsion [6] and condensing the pDNA with cationic excipients [7,8]. Other excipients that have been also used to improve pDNA stability are lactose [6] and buffering agents such as NaHCO 3 and Na 2 HPO 4 [9].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] In the pharmaceutical arena, microspheres have been shown to protect sensitive macromolecules from enzymatic and acid degradation and can offer additional advantages such as limiting fluctuation within therapeutic range, reducing side effects, decreasing dosing frequency and improving patient compliance. [10][11][12][13][14][15] Until recently, mucus had been assumed as an inert blanket, serving as a mechanical barrier against potentially injurious chemicals, bacteria and enzymes.…”
mentioning
confidence: 99%